PENERAPAN METODE INKUIRI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATA PELAJARAN IPA SISWA KELAS IV SD NEGERI 2 METRO BARAT TAHUN AJARAN 2010/2011 - Sumaryatun Sumaryatun (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Obstacles in the process of learning science in the fourth grade of SD Negeri 2 Metro West is caused because the learning activities have only centered on teachers to be dominated by the tendency of a lecture and assignments, so that students are not actively involved. The problem of this thesis is